XIIThe Eighteenth Century. (29th October 2018) - Dye, Jill; Smith, James A; Coffey, Bysshe Inigo; Harriman-Smith, James
Abstract: This chapter has four sections: 1. General and Prose; 2. The Novel; 3. Poetry; 4. Drama. Section 1 is by Jill Dye; section 2 is by James A. Smith; section 3 is by Bysshe Inigo Coffey; section 4 is by James Harriman-Smith.